High Modulus, Thermally Stable, and Self-Extinguishing Aramid Nanofiber Separators - Patel, Anish; Wilcox, Kathryn; Li, Zhuo; George, Ian; Juneja, Rishabh; Lollar, Christina T; Lazar, Simone; Grunlan, Jaime C; Tenhaeff, Wyatt E; Lutkenhaus, Jodie L (ACS applied materials & interfaces, 2020)
Mechanically and thermally robust separators offer an alternative approach for preventing battery failure under extreme conditions such as high loads and temperatures. However, the tradeoff between electrochemical performance and mechanical and thermal stability remains an ongoing challenge. Here, we investigate aramid nanofiber (ANF) separators that possess high moduli and self-extinguishing characteristics. The ANF separators are formed from the dissolution of bulk Kevlar® fibers and their subsequent vacuum-assisted self-assembly. Thermogravimetric analysis shows a high 5 wt% decomposition temperature of 447 oC, which is over ~175 oC higher than commercial Celgard separators. The ANF separator also possesses a high Young's modulus of 8.8 GPa, which is ~1000% higher than commercial separators. Even when dry or when soaked in battery electrolyte, the ANF separators self-extinguish upon exposure to flame, whereas commercial separators melt or drip. We show that these features, all though adventitious, present a tradeoff with electrochemical performance in which a LiNMC-based battery possessed a reduced capacity of 123.4 mA h g-1. Considering the separator holistically, we propose that the ANF separator shows an excellent balance of the combined properties of high modulus, flame-resistance, thermal stability, and electrochemical stability and might be suitable for extreme environment applications with further testing.